Glass in architecture from the pre- to the post-industrial era production, use and conservation - Wolf, Sophie; Hindelang, Laura; Giese, Francine; Krauter, Anne (Berlin/Boston Walter de Gruyter GmbH, 2024)
Glass is one of the most fascinating and versatile building materials in architectural history. The new insights into glass in architecture are the result of research at the intersection of glass production, construction technology and building culture. Coming from a variety of disciplines, the contributions bridge the divide between natural sciences, humanities and the preservation and restoration of cultural heritage. They explore the crucial role of flat glass in shaping architecture, particularly since the 18th century, and discuss the in-situ restoration of historic windows and glass façades and the importance of preserving this fragile heritage. The topics range from the manufacture of sheet glass in pre-industrial times to the possibilities of repair and reusability of insulating glazing. With contributions in English, German and French A multi-disciplinary survey of the history of the production and use of flat glass From the Roman times to the present day New insights on sheet glass as building material and cultural heritage.
Frontmatter -- CONTENTS -- INTRODUCTION. THE PRODUCTION AND USE OF GLASS IN ARCHITECTURE: A BRIEF HISTORY -- PART 1. SHEET GLASS PRODUCTION FROM PRE-INDUSTRIAL TIMES TO THE PRESENT DAY -- 1 FROM FRANCE TO FRANCONIA THE TECHNICAL INNOVATION OF CROWN GLASS -- 2 SCOTTISH WINDOW GLASS A NEW INDUSTRY IN THE 17TH AND 18TH CENTURIES -- 3 TECHNOLOGICAL INNOVATIONS AND CRAFT TRADITIONS IN THE 19TH-CENTURY BELGIAN WINDOW-GLASS INDUSTRY -- 4 DU MATÉRIAU AU PRODUIT. LE VERRE PERFORÉ -- PART 2 GLASS IN ARCHITECTURE FROM THE 18TH TO THE 21ST CENTURY -- 5 LE PLUS AGRÉABLE SPECTACLE DU MONDE. FLACHGLAS ALS PRÄGENDES ARCHITEKTURELEMENT DES DRESDNER ZWINGERS -- 6 WARUM HABEN FENSTER HOLZSPROSSEN?. EINE SPURENSUCHE -- 7 THE GLASS HOUSE OF ANTOINE DE PARIS -- 8 IDEOLOGIE UND BAUPRAXIS. VOM ANEIGNUNGSPROZESS DES GLASES IN DER ARCHITEKTURMODERNE -- 9 SYMBOLIC TRANSPARENCY. GLASS IN THE REPRESENTATIVE CORPORATE ARCHITECTURE OF THE 20TH CENTURY -- 10 ÉMALIT® THE CHALLENGE POSED BY A TEMPERED AND ENAMELLED SHEET GLASS FOR THE GLASS FAÇADE -- 11 LE CURTAIN WALL À L'EUROPÉENNE. HISTOIRE, TECHNIQUES ET SAUVEGARDE DES VITRAGES ANTISOLAIRES -- PART 3 THE CHALLENGE OF PRESERVATION AND IN SITU-RESTORATION OF WINDOW GLASS -- 12 ALTGLAS? ANMERKUNGEN ZUM UMGANG MIT FLACHGLAS BEI BAUDENKMALEN -- 13 DIE MONDSCHEIBENVERGLASUNG DER KLOSTERKIRCHE ST. MICHAEL IN BAMBERG. WÜRDIGUNG, VORPROJEKT UND RESTAURIERUNG DER BAROCKEN BLANKVERGLASUNG IM RAHMEN DER GESAMTINSTANDSETZUNG -- 14 NEUES GLAS IN ALTER UMGEBUNG. EIN BLICK AUF DAS BAUEN IM BESTAND SEIT 1900 -- 15 PROBLÉMATIQUE DE LA CONSERVATION-RESTAURATION DES VERRES IMPRIMÉS EMPLOYÉS DANS LE DOMAINE ARCHITECTURAL EN FRANCE -- 16 EIN PRAXISORIENTIERTER LEITFADEN FÜR DEN RESSOURCENSCHONENDEN UMGANG MIT HISTORISCHEN GLÄSERN UND FENSTERN PROFANER GEBÄUDE -- 17 DIE ERHALTUNG VON BEMALTEN ISOLIERGLASSCHEIBEN IM SCHWIMMBAD VON STUTTGART-FEUERBACH. EINE RESTAURATORISCHE UND TECHNOLOGISCHE HERAUSFORDERUNG -- 18 INNOVATIONS IN INSULATED GLAZING IN THE 21ST CENTURY. MATERIAL AND TECHNICAL BARRIERS TO REPARABILITY AND RECYCLABILITY -- BIOGRAPHIES OF CONTRIBUTORS -- IMAGE CREDITS
Keywords: Glass construction -- History; Architectural glass .